An Analysis of Motivation in Three Self-Determination Curricula. (August 2017) - Sinclair, James; Bromley, Katherine W.; Shogren, Karrie A.; Murray, Christopher; Unruh, Deanne K.; Harn, Beth A.
Self-determination skill development is a central construct in the field of secondary special education. Recently, there has been discussion to revisit the motivational theoretical roots that influence the conceptualization of self-determination in special education, and merge motivational theories with instructional practices. Self-determination can be taught in a variety of formats, but one popular means is through self-determination curricula. To determine how motivational theories are reflected in self-determination instruction, a curriculum analysis was completed. Three motivational theories (contextual theory, self-determination theory, achievement goal theory) and three self-determination curricula (Steps to Self-Determination, Whose Future Is it Anyway?, and ME! Lessons for Teaching Self-Awareness and Self-Advocacy) were analyzed. Results indicated variability of the presence of motivational theory across curriculum.